2010
DOI: 10.1038/ni.1970
|View full text |Cite
|
Sign up to set email alerts
|

Uracil residues dependent on the deaminase AID in immunoglobulin gene variable and switch regions

Abstract: Activation-induced deaminase (AID) initiates diversity of immunoglobulin genes through deamination of cytosine to uracil. Two opposing models have been proposed for the deamination of DNA or RNA by AID. Although most data support DNA deamination, there is no physical evidence of uracil residues in immunoglobulin genes. Here we demonstrate their presence by determining the sensitivity of DNA to digestion with uracil DNA glycosylase (UNG) and abasic endonuclease. Using several methods of detection, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 55 publications
1
105
0
Order By: Relevance
“…Other biochemical studies that substantiate AID's role as a DNA deamination enzyme include the observations that AID is found to be associated with transcriptionally active switch sequences in CSR-stimulated primary B cells via chromatin immunoprecipitation (ChIP) assays ) and a recent study that revealed the presence of deoxyuracil residues at regions of AID-generated mutations, thereby contributing to the already impressive volume of evidence that points toward AID as a DNA cytidine deaminase in B cells (Maul et al 2011). …”
Section: Discovery Of Aid As 'B-cell Mutator Factor'mentioning
confidence: 99%
“…Other biochemical studies that substantiate AID's role as a DNA deamination enzyme include the observations that AID is found to be associated with transcriptionally active switch sequences in CSR-stimulated primary B cells via chromatin immunoprecipitation (ChIP) assays ) and a recent study that revealed the presence of deoxyuracil residues at regions of AID-generated mutations, thereby contributing to the already impressive volume of evidence that points toward AID as a DNA cytidine deaminase in B cells (Maul et al 2011). …”
Section: Discovery Of Aid As 'B-cell Mutator Factor'mentioning
confidence: 99%
“…Second, modified bases within the DNA context are targeted principally by base excision repair [17] and, in some cases, by the mismatch repair machinery [18], or, rarely, by nucleotide excision repair [19] as well. Recently, it has became evident that the cellular 'infrastructure' for base excision and mismatch repair is also exploited in signal transduction leading to immunoglobulin gene diversification and active DNA demethylation [20][21][22][23][24]. Hence, the distinction between the harmful versus signalling role of modified bases becomes less clear and such definitions require an assessment of the cellular context (cell status, developmental stage, cell cycle stage, etc.)…”
Section: Non-orthodox Bases In Dna: Production and Eliminationmentioning
confidence: 99%
“…Powerful genetic evidence for the role of the base excision repair (BER) machinery in the processing of AID-induced DNA lesions stems from the identification of mutations in the gene encoding uracil DNA glycosylase, UNG, from a subset of hyper-IgM syndrome patients (Imai et al, 2003). Furthermore, genetic ablation of UNG in mice leads to the detection of uracil in the DNA of immunoglobulin genes, a significant increase in transition mutations at dC/dG pairs without affecting dA/dT pairs, and reduced SHM and CSR (Maul et al, 2011;Rada et al, 2002). These data suggest that uracil excision at Igh-V and switch regions is inhibited by UNG deficiency and that replication over increased dU/dG lesions leads to dT/dA mutations (Figure 3).…”
Section: Molecular Cellmentioning
confidence: 99%